Pengaruh Beban Puncak dan Beban Minimum Terhadap Kinerja Turbin Gas pada GT 2.2 PLTGU Sengkang - Muh Raehan Muyassar; Hamzah, Nur; Mulyadi, Musrady (Politeknik Negeri Ujung Pandang, 2026)
This study aims to analyze the effect of load variations, particularly peak load and minimum load conditions, on the performance of the gas turbine unit GT 2.2 at the Sengkang Combined Cycle Power Plant (Sengkang CCPP). The research method involves calculating the Heat Rate (kcal/kWh) and the thermal efficiency of the gas turbine (ηGT) based on field measurement data including key parameters such as fuel gas flow rate, power output (MW), and high heating value (HHV). The results show that gas turbine efficiency increases with higher operating loads. When operating at minimum load, the efficiency tends to be low, ranging from 17–19%, and even drops to 9% under extreme conditions (April 15, 2025). Under peak load conditions, the gas turbine efficiency increases significantly, reaching 34–37%. It can be concluded that the performance of the GT 2.2 gas turbine at PLTGU Sengkang is strongly influenced by load variation. Keywords: Gas turbine, thermal efficiency, peak load, minimum load, Heat Rate, PLTGU Sengkang.